Development and Initial Validation of the Communication About Medication by Providers-Parent Scale (CAMP-P) - Eva Igler MA; Ellen Sejkora MS; Rachel Greenley PhD; Jill Plevinsky PhD; Lindsey Bugno MS; Samantha Carreon MS; W. Hobart Davies PhD (SAGE Publishing, 2019)
This study evaluated the psychometric properties of the Communication about Medication by Providers-Parent Scale (CAMP-P), a 24-item measure of communication relevant to medication adherence between parents and medical providers. Parents of youth (ages 2-7 years) who had received a prescription within the last 12 months completed online surveys regarding demographic and appointment variables, and child's recent prescription medications, and they completed the newly developed CAMP-P. Exploratory factor analysis of CAMP-P identified 20 items about provider communication corresponding to 3 distinct scales: medication administration strategies, encouraging communication, and addressing barriers to medication taking. Factor scales were related to appointment variables, such as length of time spent discussing medications. The CAMP-P demonstrated good internal consistency and convergent and divergent validity. The CAMP-P is a novel, validated measure of parent perceptions of medication communication and can be utilized to evaluate parent-provider communication on pediatric medication adherence in clinical and research settings.